Improving Public Procurement Collusion Detection With Graph-based Machine Learning Methodologies - Santos, Everton Schneider dos; Castro, Márcio; Carvalho, Jonata Tyska (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
Public procurement is a complex process often susceptible to corruption and Machine Learning (ML) has emerged as a promising approach to identifying fraud in public procurement. While many ML methods for fraud detection rely on tabular data, information from the network of relationships between the entities involved in procurement process remains underutilized. This work aims to fill this gap with a study of ML methodologies for detecting collusion in public procurement using data extracted from the relationships network. Enriching the “Operation Car Wash” with topological information extracted from graphs helped improve the results by 1% and decrease the variability of the evaluated models by almost 5%.